Marketing Strategy for Hotel Rooms in East Luwu Regency, South Sulawesi Province - Wayan Suardana; Aris Baharuddin; Masri Ridwan (PINISI Discretion Review, 2022)
This research aims to determine the room marketing system and how effective the room marketing system is to increase hotel room sales in the East Luwu Regency. The results of the research (1) The marketing system carried out by the management of Hotel I Lagaligo Malili, Hotel Tonapa Prince Sorowako, Mireya Hotel Sorowako, Duta In Hotel Sorowako, Transisko Hotel Sorowako, Lusiana Hotel & Restaurant Sorowako, Golden House Malili, Wisma Emperor Malil, Wisma Arya and Alya Malili, Anugrah Malili Inn in East Luwu Regency, is to provide discounts to guests who often stay overnight, upgrade rooms, use social media, Instagram, and Facebook. (2) Effectiveness of hotel room marketing in Luwu Regency, the average room sales per month in 2022 are: (1) I Lagaligo Malili Hotel Rp. 206.066667,- (2) Tonapa Prince Sorowako Rp. 47.600.000,- (3) Mireya Hotel Sorowako Rp. 77,175,000, - (4) , Ambassador In Hotel Sorowako Rp. 69.150.000,- (5) Transisko Hotel Sorowako Rp. 27,454,1667, - (6) Lusiana Hotel & Restaurant Sorowako Rp. 509.750.000,- (7) Golden House Malili Rp. 108,000,000,-,(8) Wisma Emperor Malili Rp. 18,900,333,-(9) Wisma Arya and Alya Malili Rp. 33,208,333,- and ,(10) Anugrah Malili Inn generated sales of Rp. 33,208,333,- SWOT analysis results. The marketing strategy of 10 hotel rooms in East Luwu Regency, namely: Strengths (S): Increasing online and offline promotions. Weaknesses (W): Lack of Cooperation between government and companies. Threats (T): Potential competition in new markets. Opportunities (O): Opening a visit to the tourist attraction of Lake Towoti by PT. Vale Sorowako